Study of water mixing in the coastal waters of the western Taiwan Strait based on radium isotopes. (February 2016) - Men, Wu; Jiang, Yuwu; Liu, Guangshan; Wang, Fenfen; Zhang, Yusheng
Abstract: Radium is considered to be a useful tracer for studying the physical processes of seawater. In this work, three naturally occurring radium isotopes, 224 Raex, 226 Ra and 228 Ra, were measured in the coastal zone of the western Taiwan Strait during the summer seasons. Based on the distributions of the three radium isotopes and the salinity, we conclude that the water mixing pattern in the study area in summer consists of diluted water flowing from the Jiulong River to the open sea towards the east and southeast, and open sea seawater flowing inward from south to north. The submarine ground water discharges in the estuarine region, as suggested by the radium and salinity data. The residence times of the Jiulong River estuary, ranging from 7 to 49 d, were estimated using the radium isotope pairs 224 Raex and 226 Ra. Highlights: The water mixing pattern in the study area was indicated by radium and salinity. A region of submarine groundwater discharge was indicated by 224 Ra and salinity. The residence time at the estuarine station ranged from 7 to 49 days.